Opportunistic partner choice among arctic plants and root-associated fungi is driven by environmental conditions - Parisy, Bastien; Schmidt, Niels M.; Cirtwill, Alyssa R.; Villa-galaviz, Edith; Tiusanen, Mikko; Siren, Jukka; Klutsch, Cornelya F. C.; Aspholm, Paul Eric; Raundrup, Katrine; Vesterinen, Eero J.; Wirta, Helena; Roslin, Tomas (John Wiley & Sons, 2026)
Interactions between plants and soil microbes play a key role in structuring plant communities. In a rapidly changing Arctic environment, we urgently need to uncover how these interactions are responding to environmental changes. Here, we disentangle two contributions to variation in plant–fungus interactions along geographic and environmental gradients of the Arctic: abiotic impacts on the pool of fungal species present in the soil, and abiotic and biotic impacts on variation in the pool of fungi associated with plant roots. Given the low species richness and harsh conditions in the Arctic, we expected opportunistic associations to emerge, along with strong impacts of the environment on interaction structure. Across multiple spatial scales, we sampled roots of 12 widely distributed plant taxa. To characterize the pool of species available for colonization, we quantified the pool of fungi present in the soil, and to characterize realized interactions, we quantified root-associated fungal communities. Data from DNA metabarcoding of each fungal community were modeled by Hierarchical Modeling of Species Communities (HMSC). To determine whether the realized networks deviated from random expectations, we compared the observed networks to those expected under null models. Overall, we found strong support for opportunistic associations, along with some level of selectivity. Fungal communities within the soil and rhizosphere shared 85% of their fungal genera, but the composition of these communities significantly differed among ecosystem compartments. The two compartments showed similar responses to the environment, with low levels of partner fidelity among both plant and fungal taxa. Plant–fungus networks showed a distinctly nonrandom structure, which was driven by gradients in pH and temperature. Across the Arctic, the structure of fungal communities in the plant rhizosphere is thus mainly driven by abiotic rather than by biotic conditions (i.e., host identity or microbes–microbes associations). Environmental conditions will dictate what interaction partners occur where, but interactions among locally occurring plants and fungi are dominated by opportunistic partner choice. Overall, our findings suggest that the dynamics and structure of plant–root-associated interactions will be altered by abiotic changes in the Arctic realm, and that the flexibility of associations may contribute to the resilience of the system.